Hydrothermal Synthesis, Structure Investigation, and Oxide Ion Conductivity of Mixed Si/Ge-Based Apatite-Type Phases - Li, Henan (2016)
Apatite-type oxides ([AI4][AII6][(BO4)6]O2), particularly those of the rare-earth silicate and germanate systems, are among the more promising materials being considered as alternative solid oxide fuel cell electrolytes. Nonstoichiometric lanthanum silicate and germanate apatites display pure ionic conductivities exceeding those of yttria-stabilized zirconia at moderate temperatures (500–700 °C). In this study, mixed Si/Ge-based apatites were prepared by hydrothermal synthesis under mild conditions rather than the conventional solid-state method at high temperatures. Single-phase and highly crystalline nanosized apatite powders were obtained with the morphology changing across the series from spheres for the Si-based end member to hexagonal rods for the Ge-based end member. Powder X-ray and neutron analysis found all of these apatites to be hexagonal (P63/m). Quantitative X-ray microanalysis established the partial (<15 at%) substitution of La3+ by Na+ (introduced from the NaOH hydrothermal reagent), which showed a slight preference to enter the AI 4f framework position over the AII 6h tunnel site. Moreover, retention of hydroxide (OH–) was confirmed by IR spectroscopy and thermogravimetric analysis, and these apatites are best described as oxyhydroxyapatites. To prepare dense pellets for conductivity measurements, both conventional heat treatment and spark plasma sintering methods were compared, with the peculiar features of hydrothermally synthesized apatites and the influence of sodium on the ionic conductivity considered.